Towards Student Well‑being and Quality Services in Student Affairs in Africa (Journal of Student Affairs in Africa, 2021)
Two themes define this issue of the Journal of Student Affairs in Africa: student well-being, and the provision of quality Student Affairs services. The themes of student well-being in general, and mental health in particular, have become prominent in higher education in recent years, and Student Affairs is implicated in the solutions. In this issue, a more systemic approach – with less hyperbolic and reductionist notions – is put forward to illuminate not only the incidences, but also the contributing factors to student mental health and well-being along with its correlates in academic achievement and recommendations for intervention. The articles in this group cover the topic broadly and inclusively across the fully student lifecycle and from different theoretical, methodological and empirical standpoints.